Considerations and recommendations for assessment of plasma protein binding and drug–drug interactions for siRNA therapeutics. Issue 11 (10th June 2022) - Humphreys, Sara C; Davis, John A; Iqbal, Sajida; Kamel, Amin; Kulmatycki, Kenneth; Lao, Yanbin; Liu, Xiumin; Rodgers, John; Snoeys, Jan; Vigil, Adam; Weng, Yan; Wiethoff, Christopher M; et al.
Abstract: At the time of writing, although siRNA therapeutics are approved for human use, no official regulatory guidance specific to this modality is available. In the absence of guidance, preclinical development for siRNA followed a hybrid of the small molecule and biologics guidance documents. However, siRNA differs significantly from small molecules and protein-based biologics in its physicochemical,  absorption, distribution, metabolism and excretion properties, and its mechanism of action. Consequently, certain reports typically included in filing packages for small molecule or biologics may benefit from adaption, or even omission, from an siRNA filing. In this white paper, members of the 'siRNA working group' in the IQ Consortium compile a list of reports included in approved siRNA filing packages and discuss the relevance of two in vitro  reports—the plasma protein binding evaluation and the drug–drug interaction risk assessment—to support siRNA regulatory filings. Publicly available siRNA approval packages and the literature were systematically reviewed to examine the role of siRNA plasma protein binding and drug–drug interactions in understanding pharmacokinetic/pharmacodynamic relationships, safety and translation. The findings are summarized into two decision trees to help guide industry decide when in vitro  siRNA plasma protein binding and drug–drug interaction studies are warranted.